PERSPECTIVE OF PATIENTS TREATED WITH AGING IN ACUPUNCTURE (Fiep Bulletin - online, 2016)
Objective: The aim of this study was to analyze what the prospect of aging in patients treated with acupuncture. Materials and Methods: This was a qualitative study of descriptive-exploratory, where the data collection was conducted through interviews consisting of a guiding question, "Because (a) you (a) think you will be dealing with aging Acupuncture?". The answers to that question were recorded and later transcribed verbatim. After a thorough reading of the material collected, the common points of the speeches were grouped into categories and further analyzed and discussed. Results and Discussion: twelve patients of both sexes were subjects in this study aged between 40 and 57 years. Through the analysis of interviews two categories "Aging without using too much medication" and "Way of Healthy Aging" were established. Final Considerations: From the speeches obtained through the interviews, it was observed from this study that the respondents believe in the contribution of acupuncture to a healthier aging and reduce the number of medications used. It is hoped that the results of this research serve as motivation for future research on the subject.
Keywords: acupuncture; aging; qualitative research.